Kościół katolicki w Zielonej Górze przed konfliktem w maju 1960 roku = Catholic Church in Zielona Góra before the conflict in may 1960 - Zaradny, Ryszard (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper discusses the origin, development and characterization of the relationship between Catholic Church and its structure in Zielona Gora and the local authorities. The background of the relationship was the relationship between the authorities and Catholic Church in Poland, in particular during the post-war domination of the pro-Soviet left. The author analyses the actions taken by both sides of the conflict. "The priests - patriots" played an important role in this regard - they undertook efforts to destroy the Church structures from the inside. The course of the conflict was influence by the attitude of Fr. K. Michalski and dismissing him from the position of the parish priest of St. Hedwig`s Church in Zielona Góra.
Keywords: kościół katolicki; Zielona Góra (okręg) - historia; kościół katolicki - Zielona Góra - historia; stosunki państwo-kościół; od 1945 r.